Size and activity of the root meristem: A key for drought resistance and a key model of drought‐related signaling. Issue 1 (20th January 2022) - Verslues, Paul E.; Longkumer, Toshisangba
Abstract: Plants make many adjustments to their growth and development in response to even small changes in water availability. Under such conditions, root elongation can be actively restricted by stress‐related signaling mechanisms. Here we look at how the Arabidopsis thaliana root meristem can be affected by moderate water limitation (low water potential, ψ w ). Recent characterization of the clade E Growth‐Regulating (EGR) protein phosphatases and Microtubule Associated Stress Protein 1 (MASP1) provides an example of how active restriction of root meristem size allows the plant to downregulate root elongation during low ψ w stress. EGR2 protein accumulation in cortex cells of the transition zone at the distal end of the root meristem illustrates how the balance of cell division versus cell expansion signals at this critical location can determine meristem size and root elongation during low ψ w . These characteristics of EGRs also raise the question of whether they may also be involved in hydrotropism, and, more broadly, whether hydrotropism is a distinct response or a specific manifestation of more general mechanisms used to adjust root growth under moderate severity low ψ w whether or not a gradient of water availability is present. These questions, as well as a better understanding of how specific cell layers (cortex and endodermis) seem to have an outsized role in growth regulation and better understanding the roles of plasma membrane‐based signaling and polar‐localized proteins in the regulation of root meristem size and cell division activity are key to elucidating the cellular mechanisms that determine root growth behavior during soil drying.